UNRESTRICTED USE OF SPECIAL KNOWLEDGE IS A PREREQUISITE FOR COUNTERING ESPECIALLY DANGEROUS CRIMES IN THE CONTEXT OF DIGITALIZATION AND INFORMATIZATION OF SOCIETY AND THE STATE - KHRUSTALEV Vitaly Nikolaevich (Правовое государство: теория и практика, 2023)
The current task of the Russian Federation is the effective counteraction to especially dangerous crimes in the context of digitalization and informatization of society and the state using the special knowledge of specialists and experts. Purpose: to analyze the problems of using special knowledge in legal proceedings, often associated with the unacceptably low competence of their carriers - knowledgeable persons. Methods: empirical methods of comparison, description, interpretation; theoretical methods of formal and dialectical logic; specific scientific methods: legal-dogmatic and interpretation of legal norms. The study reveals that in our country the line between the special knowledge possessed by knowledgeable persons (specialists and experts), and the legal knowledge possessed by investigators, judges, etc., is consistently blurred. It is proved by the inclusion of the specialty «forensics» in the enlarged group of legal specialties and the subsequent approval in 2020 of the Federal Educational Standard for this specialty of the 3++ generation, in which, compared to previous generations of the Federal State Educational Standards of Higher Professional Education, a significant proportion of special knowledge is replaced by legal knowledge, making it virtually impossible to provide high-quality training for future specialists and experts. The development of a professional standard for a forensic expert for the benefit of forensic organizations may have a positive impact on the professionalism of their staff, but the draft of this standard fixes the need for them to have a predominance of legal knowledge, which is directly contrary to the interests of law enforcement in the country in the due professionalism of forensic experts, designed to contribute to the effectiveness of scientific and technical support for the detection and investigation of crimes. Proposals for improving the situation are formulated.